Two new species of Aspidistra (Asparagaceae, Nolinoideae) from northern Vietnam: A. clausa and A. triradiata - Vislobokov, Nikolay Aleksandrovich (Phytotaxa, 2015)
Aspidistra clausa and Aspidistra triradiata are described and illustrated as new species from northern Vietnam (Vinh Phuc province, Tam Dao National Park). Aspidistra clausa is similar to A. crassifila, but has narrower leaves (lamina 2.8–4.5 cm vs. 6–12 cm), perigone tube wide tubular vs. campanulate, appendages longer, stigma conical vs. mushroom-shaped. Aspidistra triradiata is similar to A. hainanensis, but flowers larger (1.8–2.4 cm long, Ø 1.8–2.8 cm vs. 1–1.2 cm long, Ø 1.3–1.5 cm), perigone urceolate, lobes with 4 verrucose keels, stigma with three purple radial lines.